Control Valve Testing During Operation - Kokas, R. (International Journal of Engineering and Management Sciences, 2017)
The most commonly used control technology in building engineering is mixing. The purpose of the measurement is to find out what effects have the different control valve position combinations on the system. How the mixing efficiency changes in these cases.